PEMBEKALAN SIKLUS AKUNTANSI PERUSAHAAN JASA TERHADAP SISWA-SISWI SMA PELITA KASIH JAKARTA - Marcella, Maissy Moria; Sastrasasmita, Emillia (Jurnal Serina Abdimas, 2024)
The MBKM team carries out training on assistance activities in educational units. The MBKM team carried out this activity with the intention of being a lecture activity. The partner is SMA Pelita Kasih Jakarta. The first step was to carry out a survey to find the problems faced by partners, namely SMA Pelita Kasih Jakarta. The problem that partners found in the accounting material at Pelita Kasih High School was that they journaled transactions incorrectly and they had not received in-depth service company accounting material. The basic foundation in understanding accounting is the ability to journal transactions correctly. The solution provided by the teaching team to partners is theoretical provision about journals and discussion of accounting questions in service companies. The purpose of this visit is to look for partner problems. Based on the results of discussions with the school, the problem partners face in studying accounting subjects is difficulty in understanding service company accounting. Based on the Education Unit Level Curriculum (KTSP), the accounting material for service companies is the application of the service company accounting cycle which begins with recording evidence of transactions, and ends with the preparation of financial reports consisting of a balance sheet, profit and loss report and capital changes report. To complete the training process, the teaching team created modules related to theory and examples as well as practice questions. Training is provided face-to-face at Pelita Kasih High School, Jakarta.